Assembling Fairtrade: Practices of progress and conventionalization in the Chilean wine industry. (February 2019) - Herman, Agatha
The global Fairtrade system is multiple, heterogeneous and dynamic. The processes that underlie its contextual formations are key, and this paper analyses these through bringing together assemblage thinking and social practices to discuss Fairtrade in the Chilean wine industry. Local-level contestations and appropriation highlight the different forms Fairtrade takes at the micro-scale, which maintain a contextual heterogeneity without challenging the overall coherence of the Fairtrade economy. Power relations are uneven and the important role of local and international 'assemblage converters' in catalysing and curtailing possibilities for Fairtrade practices is highlighted. These operate within and across scales, interacting, and varyingly integrated, with other similarly multi-scalar assemblages to support or disrupt particular stabilized compositions. Fairtrade emerges as simultaneously globally coherent and locally fragmented, a system in constant motion between alternative and conventional relations and practices. To challenge creeping conventionalization, the paper concludes that maintaining space for unpredictability and creativity is critical to Fairtrade's future through making space for enhancing opportunities and for alternatives to take flight.